Isolation, structural elucidation and in vitro hepatoprotective activity of flavonoids from Glycyrrhiza uralensis - Cheng, Ming; Ding, Liqin; Kan, Hongfeng; Zhang, Hongmin; Jiang, Benke; Sun, Yingjie; Cao, Shijie; Li, Wei; Koike, Kazuo; Qiu, Feng (Journal of Natural Medicines, 2019)
Two new flavonoid glycosides, 2′,4′-dihydroxydihydrochalcone-4- O - β - d -glucopyranoside ( 1 ) and medicarpin-3- O - β - d -apiofuranosyl (1 → 2)- β - d -glucopyranoside ( 2 ), together with 34 known flavonoids were isolated from the 75% EtOH extract of the dried roots of Glycyrrhiza uralensis Fisch. Their structures were elucidated on the basis of spectroscopic analyses. The flavonoids were classified into ten sub-types, namely, dihydrochalcone ( 1 ), pterocarpans ( 2 – 4 ), flavones ( 5 – 6 ), flavanones ( 7 – 11 ), chalcones ( 12 – 15 ), retro-chalcones ( 16 – 18 ), isoflavans ( 19 – 21 ), isoflavones ( 22 – 28 ), 3-arylcoumarins ( 29 – 30 ), and coumestans ( 31 – 36 ). The isolated flavonoids were evaluated for in vitro hepatoprotective activity against d -galactosamine-induced toxicity in human hepatoma HepG2 cells.